Allergic and non-allergic wheeze among farm women in the Agricultural Health Study (2005–2010). Issue 11 (8th August 2022) - Islam, Jessica Y; Mohamed, Ahmed; Umbach, David M; London, Stephanie J; Henneberger, Paul K; Beane Freeman, Laura E; Sandler, Dale P; Hoppin, Jane A
Abstract : Background: Farms represent complex environments for respiratory exposures including hays, grains and pesticides. Little is known about the impact of these exposures on women's respiratory health. We evaluated the association of farm exposures with allergic and non-allergic wheeze among women in the Agricultural Health Study, a study of farmers and their spouses based in Iowa and North Carolina. Methods: We used self-reported data (2005–2010) on current use (≤12 months) of 15 pesticides (selected based on frequency of use) and occupational farm activities from 20 164 women. We defined allergic wheeze as reporting wheeze and doctor-diagnosed hay fever (7%) and non-allergic wheeze as wheeze but not hay fever (8%) in the past 12 months. Using polytomous logistic regression, we evaluated associations of wheeze subtypes with pesticides and other farm exposures (eg, raising farm animals) using no wheeze/hay fever as the referent, adjusting for age, body mass index, state, current asthma, glyphosate use and smoking. Results: Current use of any pesticide, reported by 7% of women, was associated with both allergic (OR: 1.36, 95% CI: 1.10 to 1.67) and non-allergic (OR: 1.25, 95% CI: 1.04 to 1.51) wheeze. Four pesticides were associated with at least one wheeze subtype: glyphosate, with both wheeze subtypes; diazinon and fly spray with only allergic wheeze; carbaryl with only non-allergic wheeze. Working weekly with mouldy hay was associated with allergic (OR: 1.88, 95% CI: 1.26 to 2.80) and non-allergic wheeze (OR: 1.69, 95% CI: 1.18 to 2.42). Conclusion: Use of specific pesticides and certain farm activities may contribute to wheeze among farm women.